Nine keys for successful interprofessional collaboration Based on observing facilitators and barriers during different types of treatment meetings: A qualitative study - Simon T. de Gans; Renee C. M. A. Raijmann; Meike F. Huijbers; Natasja Looman; Marjolein van de Pol; Babette C. van der Zwaard; Huiberdina L. Koek; Marielle H. Emmelot-Vonk; Carolina J. P. W. Keijsers (PLoS ONE, 2026)
Introduction The increasing prevalence of multimorbidity requires effective collaboration between health professionals. Both interprofessional (IP) and multidisciplinary (MD) collaboration can be used for this purpose. IP collaboration refers to professionals working together toward a common patient-centred goal. In contrast, MD collaboration involves health professionals advocating for their own specialty, which may result in different disease-centred goals for the same patient. This study aims to evaluate and compare these two types of collaboration and develop recommendations for successful collaboration for patients with multimorbidity. Methods This qualitative study employed a rapid ethnographic non-participatory approach. We observed IP and MD treatment meetings using video and audio recordings to identify factors that might influence collaboration between health professionals. Data were analysed iteratively by multiple researchers using a thematic and conventional content analysis. Results There were clear differences between the observed meetings. The IP meetings had a roundtable setting, designated chair, discussions around a common patient-centred goal, active participants, and a relaxed atmosphere that facilitated interprofessional learning. Conversely, the MD meetings had a theatre design, disease-centred discussion, more passive participants, and a less relaxed atmosphere with fewer opportunities for learning. Five participants attended both settings. These participants were more actively engaged and contributed more to interprofessional learning in the IP meetings than in the MD meetings. Conclusion This study showed multiple factors that may influence collaboration and participants’ behaviour, particularly regarding active participation, learning, and patient-centred care. These factors were translated into nine keys for optimizing collaboration, which could support improvement in collaborative practice.